Homonormativity and celebrating diversity: Australian school staff involvement in gay-straight alliances. Issue 8 (3rd July 2021) - Grant, Ruby; Beasy, Kim; Coleman, Bianca
ABSTRACT: With the growing acceptance and normalisation of same-sex attraction in the West, scholars from a range of fields have documented a 'post-gay' shift, or a decline in the significance of sexual identity labels among youth. Despite this shift, lesbian, gay, bisexual, transgender, intersex and queer (LGBTIQ) youth continue to experience discrimination and harassment, particularly in schools. In this context, this article examines the role of student gay-straight alliances (GSA) or 'diversity groups' in Australian schools. Most research on GSAs focuses on student experiences in the North American context. In contrast, this article provides a unique exploration of teachers and staff involvement in school GSAs in Tasmania, Australia. Drawing on qualitative interviews with teachers and staff, this article examines staff perceptions and involvement in GSAs and the impact this may have on GSA function and success. Through thematic analysis, we identify three common situations: active GSAs, inactive GSAs, and singular event-based initiatives. We argue that neoliberal and homonormative understandings of LGBTIQ-inclusion permeate staff approaches to facilitating GSAs and impact on the potential for these groups to undertake the critical political work needed to bring about change in school contexts.